The vanishing - Little, Bentley (A Signet book, 2007)
When a wealthy CEO slaughters his whole family, leaving behind a cryptic message, and children across California fall victim to a monstrous change, social worker Carrie Daniels and reporter Brian Howells join forces to find the link between these puzzling events, which draws them even closer to unimaginable darkness and evil.